A Comprehensive Risk Assessment and Stratification Model of Papillary Thyroid Carcinoma Based on the Autophagy-Related LncRNAs - Mu, Yongrun; Song, Fuling; Yuan, Kai; Zhang, Zili; Lu, Yan; Fu, Rongzhan; Zhou, Dongsheng (Frontiers in Oncology, 2022)
Abstract: Background: Papillary thyroid carcinoma (PTC) is one of the most common malignant carcinomas in endocrine system, and it has a growing incidence worldwide. Despite the development of diagnosis and treatment modalities for thyroid carcinoma, the outcome remains uncertain. Autophagy participates in the process of cancer invasion, malignancy, metastasis, and drug resistance. Emerging research has shown that long non-coding RNAs (lncRNAs) plays an important role in the process of different types of cancers. However, the interaction between the process of autophagy and lncRNA and the value of autophagy related lncRNA for risk assessment, prediction of drug-sensitivity and prognosis prediction in PTC patients remains unknown. Materials and methods: We screened 1283 autophagy-related lncRNAs and identified 144 lncRNAs with prognostic value in the Cancer Genome Atlas（TCGA）cohorts. Univariate and multivariate Cox regression analyses were used to establish the prognosis-related autophagy related lncRNA risk classification consisted of 10 lncRNAs to indicate the level of risk, according to which the patients were grouped into high-risk group and low risk-group. Results: The high-risk group had dramatically worse overall survival compared with the low-risk group. Cox regression analysis was performed to confirm the independent prognostic value of the autophagy-related lncRNA risk stratification, and the time-dependent receiver operating characteristic curves of the risk stratification were 0.981 (1-years), 0.906 (3-years), and 0.963(5-years). lncRNA CRNDE is over expressed in the tumor and its high expression matched with poorer survival state. So, we choose it for further experiment. Finally, knock down of the CRNDE in papillary thyroid carcinoma increased the sensitivity to sorafenib. Conclusion: Collectively, we successfully established a novel risk stratification for papillary thyroid carcinoma based on the expression profiles of autophagy-related lncRNAs.